A fully coupled implementation of hydrogen embrittlement in FE analysis. (September 2019) - Gobbi, Giorgia; Colombo, Chiara; Miccoli, Stefano; Vergani, Laura
Highlights: FE open source code for simulating hydrogen embrittlement in Abaqus Hydrogen diffusion fully coupled with stress-strain during crack propagation 2D cohesive zone model predicting hydrogen effect on fracture toughness of a steel Guideline to the methodology and the use of the developed code Abstract: Proper understanding of hydrogen embrittlement in steel is of paramount importance in several engineering applications, e.g. oil & gas and hydrogen storage & transport. This phenomenon can be modelled by means of a mass diffusion analysis driven by mechanical fields, i.e. hydrostatic stress gradient and plastic strain. Since the mechanical response depends on the hydrogen content itself, continuum mechanics and mass diffusion equations are fully coupled. Accordingly in this paper a fully coupled–cohesive zone implementation is presented for the Abaqus Finite Element code, adopting the coupled thermal–stress analysis and the analogy between mass diffusion and heat transfer. The implementation requires extensive use of FORTRAN user subroutines and common blocks to share data, plus some auxiliary Python scripts. With the aim to provide a practical example to the use of the code, a FE model reproducing a fracture toughness test of C(T) specimen charged with atomic hydrogen is described. Moreover, a sensitivity analysis of the model shows the capability of the developed numerical tool in predicting hydrogen embrittlement. The code developed in this paper is open source under a permissive free software license.